2021
DOI: 10.1093/humrep/deab236
|View full text |Cite
|
Sign up to set email alerts
|

Fertility status among long-term childhood acute lymphoblastic leukaemia survivors enrolled between 1971 and 1998 in EORTC CLG studies: results of the 58 Late Adverse Effects study

Abstract: STUDY QUESTION What are the fertility outcomes of male and female childhood acute lymphoblastic leukaemia (ALL) long-term survivors? SUMMARY ANSWER We observed similar fertility outcomes in both male and female childhood ALL survivors compared with the general population, with the exception of a higher proportion of miscarriages among partners of male survivors. WHAT IS KNOWN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A total of 1418 childhood ALL survivors were eligible in the 58LAE project, among whom 507 answered to the socio-economic questionnaire and were eligible for the QoL evaluation (see earlier publication [ 30 ]). Among them, 183 responded (36.1%) and 3 additional patients provided QoL data but no socio-economic data, leading to a total of 186 respondents (109 females and 77 males).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1418 childhood ALL survivors were eligible in the 58LAE project, among whom 507 answered to the socio-economic questionnaire and were eligible for the QoL evaluation (see earlier publication [ 30 ]). Among them, 183 responded (36.1%) and 3 additional patients provided QoL data but no socio-economic data, leading to a total of 186 respondents (109 females and 77 males).…”
Section: Resultsmentioning
confidence: 99%
“…Adult survivors (≥18 years) who were diagnosed with ALL during childhood (<18 years at diagnosis) and registered in the European Organisation for Research and Treatment of Cancer (EORTC) Children Leukaemia Group (CLG) trials 58741 (1971–1978), 58831/2 (1983–1989) and 58881 (1989–1998) were eligible. Details regarding the risk-group stratification and the treatment protocols were described earlier [ 30 , 31 ] and provided in Figure S1 . Follow-up data, including QoL data, were collected from 24 institutions (10 in Belgium and 14 in France).…”
Section: Methodsmentioning
confidence: 99%
“…In this section, we provide details on definitions (i.e., CNS involvement), treatments (i.e., CRT, hematopoietic stem cell transplantation [HSCT] and high-dose cytarabine [HD Cytarabine]) and risk group (very high-risk [VHR] in study 58881) considered for the study of association with neurotoxicity (Table 1 ). Other details regarding studies 58741, 58831/2 and 58881 are reported in Supplementary Table S1) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Как противоопухолевая терапия, так и основное заболевание пациента могут привести к репродуктивной дисфункции и в дальнейшем к бесплодию. Противоопухолевое лечение может иметь как немедленные, так и отсроченные неблагоприятные последствия для репродуктивного здоровья [3]. По данным научных исследований, у взрослых пациентов, перенесших краниальную лучевую терапию и химиотерапию в связи с лечением лейкоза в детском возрасте, выявлены значительные нарушения фертильности и снижение частоты наступления беременности [4,5].…”
Section: Introductionunclassified